HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN PRESTASI AKADEMIK PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Umboh, Eunike Relsye; Kepel, Billy; Hamel, Rivelino S. (Universitas Sam Ratulangi, 2017)
Abstract : Motivasion to learn is the overall driving force in the one is able to raise the spirit orenthusiasm to learn. The learning achievementis is a result that has been obtained or achievedfrom activities that have been carried out or treated. Research purpose of this study was todetermine the relationship between learning motivasion and academic achievement in nursingscience student of the faculty of medicine at sam ratulangi university manado. Samples were 64respondents in the can by using purposive sampling technique. Research design is descriptiveanalytic with cross secrional approach and the data collected from respondents usingquestionnaires learning motivation and academic achievement questionnaire. Test using theFhiser’s Exact Test statistic with significance level α = 0,05% or 95%. Research results showedthe value of p = 0,000 < α = 0,05. The conclusion of this research that there is a relationshipbetween learning motivation and academic achievement in students of nursing science ProgramFaculty of Medicine, University of Sam Ratulangi Manado. Recommendation: Results of this studycan be used as a source of information and learning materials specifically so that students can bemotivated to learn to achieve good academic achievement, and can add a reference orbibliography for further research in order to investigate more about the motivation to learn thataffect academic achievement.Keywords : Motivation, Academic AchievementAbstrak : Motivasi belajar adalah keseluruhan daya penggerak di dalam diri seseorang yangmampu menimbulkan semangat atau kegairahan belajar. Prestasi belajar adalah suatu hasil yangtelah diperoleh atau dicapai dari aktivitas yang telah dilakukan atau dikerjakan. Tujuan penelitianini adalah untuk mengetahui hubungan antara motivasi belajar dengan prestasi akademik padamahasiswa program studi ilmu keperawatan fakultas kedokteran universitas sam ratulangi manado.Sampel berjumlah 64 responden yang di dapat dengan menggunakan teknik purposive sampling.Desain penelitian deskriptif analitik dengan pendekatan Cross Sectional dan data dikumpulkandari responden dengan menggunakan kuesioner motivasi belajar dan kuesioner prestasi akademik.Uji statistic menggunakan Fhiser’s Exact Test dengan tingkat kemaknaan α = 0,05 atau 95%. Hasilpenelitian didapatkan nilai p = 0,000 < α = 0,05. Kesimpulan dari penelitian ini yaitu terdapathubungan antara motivasi belajar dengan prestasi akademik pada mahasiswa Program Studi IlmuKeperawatan Fakultas Kedokteran Universitas Sam Ratulangi manado. Saran: Hasil penelitian inidapat digunakan sebagai sumber informasi serta bahan pembelajaran khususnya mahasiswa agardapat lebih termotivasi dalam belajar sehingga meraih prestasi akademik yang baik, dan dapatmenambah referensi atau pustaka bagi peneliti selanjutnya sehingga dapat meneliti lagi tentangmotivasi belajar yang mempengaruhi prestasi akademikKata Kunci : Motivasi Belajar, Prestasi Akademik